2023
DOI: 10.1177/10499091231154887
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Associated Factors and Adverse Outcomes of Demoralization in Cancer Patients: A Decade of Systematic Review

Abstract: Demoralization has been extensively studied in oncology and palliative care settings, and is characterized by a loss of meaning and purpose in life, a sense of powerlessness over life events, and a sense of helplessness. The objective of this systematic review is to synthesize the prevalence, associated factors, and adverse outcomes of demoralization in cancer patients by reviewing the literature of the last decade. Seven databases (PubMed, PsycINFO, Embase, Web of Science, Medline, CINAHL and Cochrane Library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Recognizing demoralization as a separate entity from depression and identifying its unique impact on patients' well-being can lead to more targeted interventions and improved outcomes. Studies have shown that demoralization is prevalent in this population, with rates ranging from 13% to 50% [12]. Demoralization often coexists with depression, anxiety, adjustment disorders, and suicidal ideation in cancer patients [12][13][14].…”
Section: Exploring the Burden Of Depression In The Cancer Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing demoralization as a separate entity from depression and identifying its unique impact on patients' well-being can lead to more targeted interventions and improved outcomes. Studies have shown that demoralization is prevalent in this population, with rates ranging from 13% to 50% [12]. Demoralization often coexists with depression, anxiety, adjustment disorders, and suicidal ideation in cancer patients [12][13][14].…”
Section: Exploring the Burden Of Depression In The Cancer Populationmentioning
confidence: 99%
“…Studies have shown that demoralization is prevalent in this population, with rates ranging from 13% to 50% [12]. Demoralization often coexists with depression, anxiety, adjustment disorders, and suicidal ideation in cancer patients [12][13][14]. While demoralization and depression share similarities, they are distinct conditions, with demoralization characterized by feelings of subjective incompetence and a lack of hope [15,16].…”
Section: Exploring the Burden Of Depression In The Cancer Populationmentioning
confidence: 99%
“…9 Additionally, the prevalence of demoralization in cancer patients is high, ranging from 13.5% to 49.4%. 10 Studies in recent years have indicated that demoralization syndrome alone, without comorbid depression, can serve as an independent risk factor for subsequent suicide risk among cancer patients. 11 The concept of demoralization originally arose from those who were suffering and their meaning-seeking as a coping strategy, as depicted by a psychiatrist.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the prevalence of demoralization in cancer patients is high, ranging from 13.5% to 49.4% 10 . Studies in recent years have indicated that demoralization syndrome alone, without comorbid depression, can serve as an independent risk factor for subsequent suicide risk among cancer patients 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with good family support and high degree of education are less likely to experience demoralization. Regardless of the type of malignancy or geographic location, the rate of demoralization among patients with cancer ranges from 13% to 49% (Ko et al, 2018; Tang et al, 2020, Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%